USING PELVIS MORPHOLOGY TO IDENTIFY SEX IN MOOSE SKELETAL REMAINS - Duetsch, Jason; Peterson, Rolf (Lakehead University, 2012)
The only published method for sex determination in even-toed ungulates (i.e., Cervidae) through the use of skeletal remains (excluding the skull) is pelvic suspensory tuberosity presence/absence in white-tailed (Odocoileus virginianus) and black-tailed deer (Odocoileus hemionus columbianus). Tuberosities are not easily distinguishable on moose (Alces alces) pelvises, even when a large number are available for comparison. Unlike in horses (Equus caballus) with similar skeletal structure as moose, pelvic inlets of moose show no distinctive sex characteristics on an individual level. Several linear angular (n = 5) and linear (n = 3) measurements were made on Isle Royale moose pelvises (n = 35). Results showed statistically significant differences between male and female pelvises for all angles, with unambiguous data collected from the angle created by the ischiatic arch (ventral brim of the ischium). As a rule of thumb, males and females exhibit an ischiatic arch angle of <90° and >90°, respectively. Two of the length measurements were also statistically different; however, overlap of these measurements would prevent their practical use. Learning more about sexing techniques will increase our forensic, archeological, and anatomical knowledge of moose anatomy and benefit sex determination in the field when only headless, scavenged, or partial carcasses remain.